Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
You have the following equation:
4x - 3 = 2x + 5
In order to solve the previous equation, proceed as follow:
4x - 3 = 2x + 5 subtract 2x both sides
4x - 2x - 3 = 5 add 3 both sides
4x - 2x = 5 + 3 simplify like terms
2x = 8 divide by 2 both sides
x = 8/2
x = 4
Hence, the solution to the given equation is x = 4
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.